Precipitation in the Madeira Island over a 10-year period and the meridional water vapour transport during the winter seasons - Couto, Flavio (2016)
In this paper, a 10-year daily accumulated precipitation analysis of Madeira highland is presented, as well as the relationship between meridional water vapour transport during 10 winter seasons and the precipitation recorded in the island during the same period. Here, the meridional water vapour transport is considered as occurring in narrow corridors known as atmospheric rivers – ARs – which were visually identified in the total precipitable water vapour field extracted from Atmospheric Infrared Sounder (AIRS) data within a domain covering the North Atlantic Ocean. European Centre for Medium-range Weather Forecasts (ECMWF) analysis was also used when necessary. Daily precipitation during the period covered by the study evidenced generally dry summers, whereas the highest values for daily accumulated precipitation were recorded mainly during the winter and also during the autumn and spring. Image analysis shows that moist air originating mainly in the Caribbean Sea flows northward or eastward, intersecting, on some occasions, the island during the winter season, often during a stage of dissipation. The orientation of the flow and the amount of water vapour transported to the island are important features, contributing to the occurrence of significant precipitation events. In fact, the moist environment created by ARs may favour the occurrence of precipitation, but this is not the sole factor favouring high rainfall over Madeira.